2021
DOI: 10.1002/eat.23621
|View full text |Cite
|
Sign up to set email alerts
|

Factor structure and psychometric properties of the Muscularity‐Oriented Eating Test in university women in Australia

Abstract: Objective: Toned muscularity continues to emerge as a salient aspect of women's body image. However, there is a dearth of research investigating the potentially maladaptive eating practices and related cognitions that accompany the drive for muscularity in women. This may be attributable to the limited empirical and clinical attention previously given to muscularity-oriented disordered eating and, accordingly, the lack of validated measures assessing these concerns. To address this knowledge gap, our study aim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 49 publications
3
9
0
Order By: Relevance
“…84 inBrazilian women(de Carvalho et al, 2022) and ω = .93 in Australian women(Cunningham et al, 2021). Moreover, the MOET also demonstrated high temporal stability in Chinese women as indicated by the large ICC value, findings consistent withde Carvalho et al (2022) showing an ICC of .92 in Brazilian women.In terms of convergent validity, we found that the MOET total scores had large correlations with thinness-oriented disordered eating as measured by the EDE-QS, drive for muscularity as measured by the FMS, and psychosocial impairment as measured by the CIA 3.0, indicating good convergent validity of the MOET in Chinese women.…”
supporting
confidence: 62%
See 2 more Smart Citations
“…84 inBrazilian women(de Carvalho et al, 2022) and ω = .93 in Australian women(Cunningham et al, 2021). Moreover, the MOET also demonstrated high temporal stability in Chinese women as indicated by the large ICC value, findings consistent withde Carvalho et al (2022) showing an ICC of .92 in Brazilian women.In terms of convergent validity, we found that the MOET total scores had large correlations with thinness-oriented disordered eating as measured by the EDE-QS, drive for muscularity as measured by the FMS, and psychosocial impairment as measured by the CIA 3.0, indicating good convergent validity of the MOET in Chinese women.…”
supporting
confidence: 62%
“…We used principal axis factoring with Oblimin rotation to extract factors. Moreover, in line with the previous studies validating the MOET in women (Cunningham et al, 2021;de Carvalho et al, 2022), we relied on both the eigenvalues >1 criterion (Kaiser, 1960) and parallel analysis (Hayton et al, 2004) to determine the number of factors. For parallel analysis, factors were retained when eigenvalues (λ) from the actual dataset were higher than the eigenvalues of the random dataset.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These items (“I have continued eating despite feeling full, in attempting to influence my muscularity” and “I have felt anxious when I run out of protein‐based supplements”) involve important factors in the construct of muscularity‐oriented eating behavior in clinical populations. Cunningham et al (2021) evaluated the MOET among university women in Australia, finding support for a more brief one‐factor scale, after excluding items 2, 9, and 10. From a clinical and practical standpoint, it might be confusing for clinicians and researchers to have two separate MOETs.…”
Section: Discussionmentioning
confidence: 99%
“…It is interesting to note that muscularity concerns have also been documented among women (Campos et al, 2021; Carvalho et al, 2019; Girard et al, 2018; Rodgers et al, 2018), highlighting the need to develop instruments capable of assessing these body image concerns and muscularity‐oriented disordered dietary practices in women. Cunningham et al (2021) recently evaluated the MOET among university women in Australia, finding support for a briefer (12‐item) one‐factor scale. Because the drive for muscularity can be a precursor of disordered eating and lead to severe biopsychosocial complications in both men and women, the development of specific instruments for its evaluation is fundamental for future research on disordered eating prevention and treatment.…”
Section: Introductionmentioning
confidence: 99%